2011
DOI: 10.1084/jem.20101757
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of mast cell degranulation versus cytokine secretion by the actin regulatory proteins Coronin1a and Coronin1b

Abstract: Coronin1a inhibits mast cell degranulation through actin cytoskeletal dynamics while augmenting cytokine secretion, an effect exacerbated by additional loss of Coronin1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 33 publications
8
48
0
Order By: Relevance
“…These results, together with the observation of a localized clearance of actin cytoskeleton at the degranulatory synapse, provide a mechanistic link between localized signalling and polarized secretion. Accordingly, actin cytoskeleton disassembly was previously reported in rodent mast cells stimulated with soluble antigens 41,44 . This process was proposed to allow mast cell granules to cross the cortical actin ring and reach plasma membrane 45 .…”
Section: Discussionmentioning
confidence: 74%
“…These results, together with the observation of a localized clearance of actin cytoskeleton at the degranulatory synapse, provide a mechanistic link between localized signalling and polarized secretion. Accordingly, actin cytoskeleton disassembly was previously reported in rodent mast cells stimulated with soluble antigens 41,44 . This process was proposed to allow mast cell granules to cross the cortical actin ring and reach plasma membrane 45 .…”
Section: Discussionmentioning
confidence: 74%
“…that had been found to not be sensitized to food ( Figure 2C). The appearance of lysosomal-associated membrane protein 1 (LAMP-1) at the cell surface of mast cells is an established surrogate marker for antigen/IgE-mediated histamine release (28,29), and we found that WT mast cells loaded with serum from food-sensitized Was -/-mice degranulated in response to stimulation with an antigen extract from conventional chow, but not in response to an extract from a protein-free, amino acid-based elemental diet ( Figure 2C). In contrast, mast cells loaded with serum from nonfood-sensitized animals were not activated by either food extract, which further demonstrated that IgE-dependent degranulation was antigen specific and established that screening of antibody IgG1 was observed (Supplemental Figure 1D).…”
Section: Sensitization To Food Antigens and Food Allergy Are Enrichedmentioning
confidence: 99%
“…Exocytosis involves the continuous reorganization of the actin cytoskeleton (13,45), and the function of many Rabs is linked with actin rearrangements (19). Therefore, to explore the potential role of the actin skeleton in mediating Rab regulatory functions on exocytosis, we repeated our screen in the presence of cytochalasin D that disrupts the actin cytoskeleton by inhibiting actin polymerization.…”
Section: The Role Of Actin In Mediating Rab Network Regulatory Functmentioning
confidence: 99%